Understanding Psychopathy Using the Basic Elements of Personality. Issue 5 (May 2015) - Miller, Joshua D.; Lynam, Donald R.
Abstract Psychopathy is a form of personality disorder characterized by arrogance, self‐absorption, callousness, exploitation, and impulsivity that is also strongly associated with antisocial behavior. The present paper argues that psychopathy can and should be understood as a configuration of personality traits from a general model of personality functioning – the five‐factor model (FFM). In this paper, we demonstrate that previous theoretical conceptualizations of psychopathy and current empirical ones converge on a general FFM profile characterized by very low scores on agreeableness and conscientiousness and mixed relations to aspects of neuroticism and extraversion. Further, we articulate the advantages to understanding psychopathy in this way. The FFM provides an assay of extant inventories, explains the factor structure of various inventories, accounts for the epidemiology of psychopathy, and makes sense of the litany of putative psychopathic deficits. Perhaps most importantly, the FFM provides a connection to basic research in personality.